PERILAKU HARIAN ORANGUTAN (Pongo pygmaeus Linnaeus) DALAM KONSERVASI EX-SITU DI KEBUN BINATANG KASANG KULIM KECAMATAN SIAK HULU KABUPATEN KAMPAR RIAU - Astriana Pujacita Suhandi; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Orangutan is an endangered species. One of the efforts to prevent the extinction of the orangutan is the ex-situ’s conservation for example zoo. The purpose of this research to determine the daily behavior and the duration of activity of orangutan in habitat at ex-situ in Kasang Kulim’s Zoo and to know the difference of frequency daily activities of orangutan by age class. The research was conducted in the month of August-September 2014. The objects of this research are five orangutan. The research method was descriptive statistics. The type of this research is observation. Based on the research results, the daily behavior of orangutan at Zoo Kasang Kulim consists of: the behavior of eating, the behavior of moving, the behavior of resting, the behavior of social, the behavior of the play itself, and other behaviors (grooming and shitting). Total of activity time orangutans obtained during 25 days of observation is 14 876 minutes. The highest behavior shown in the behavior of the resting (10 216 minutes or 69% of total daily activity orangutan). The frequency of daily behavior based on age class with a long observation period of 10 hours every day. The frequency of the behavior of resting at age class of adults and adolescents the highest frequency are 67 times / day and 71 times / day, while the frequency of the behavior of moving at baby age class the highest frequency that is 116 times / day. Keywords: Daily Behavior, Orangutan, Ex-situ’s Conservation